"Żyć i umrzeć w Los Angeles" Williama Friedkina - wielkomiejski mikrokosmos lat 80. = William Friedkin`s "To live and die in L.A." - the urban microcosm of the 1980s - Prusinowski, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
William Friedkin achieved success with "The French Connection" (1971), which was a milestone in the history of crime cinema thanks to his proficiency in filming dynamic action sequences in the urban setting. According to the American director, in the scenery of the grim and shapeless "concrete jungle" the lines between good and evil tend to blur and policemen often become similar to criminals.
Keywords: film amerykański; kryminał; 20 w.